The Effect of Outdoor Learning Math Using Gps-Based Mobile Technology-Assisted Mathematics Traces on Junior High School Students' Problem-Solving Ability and Mathematical Communication Skills - Demma Papiang, Restu; Susanti, Mathilda (International Journal of Studies in International Education, 2025)
The purpose of this study is to describe the effect of Outdoor Learning Math using GPS-based mobile technology-assisted math traces on students' problem solving and mathematical communication skills, describe the effect of Outdoor Learning Math using GPS-based mobile technology-assisted math traces on problem solving skills, and describe the effect of Outdoor Learning Math using GPS-based mobile technology-assisted math traces on students' mathematical communication skills. This type of research is Quasi Experimental using Nonequivalent Control Group Design. This research was conducted at SMP Negeri 1 Malinau, North Kalimantan City with 60 students from two 9th grade classes. The instruments used in this study were descriptive test questions of problem solving ability, mathematical communication and observation sheets for the implementation of Outdoor Learning Math learning activities using GPS-based mobile technology-assisted math traces. The results showed that there was an effect of Outdoor Learning Math using GPS-based mobile technology-assisted math traces on students' problem solving and mathematical communication skills together, there was no effect of Outdoor Learning Math using mobile technology-assisted math traces on problem solving skills, and there was no effect of Outdoor Learning Math using GPS-based mobile technology-assisted math traces on mathematical communication skills. Therefore, for future researchers to expand the scope of materials such as geometry, statistics and probability, algebra, arithmetic and add student motivation variables.